Pengaruh Leverage terhadap Kebijakan Dividen dengan Firm Size dan Profitabilitas sebagai Variabel Mediasi pada Perusahaan Sektor Agrikultur di BEI Tahun 2014-2018 - Mia Wahyu Nuraini (Jurnal Ilmu Manajemen, 2021)
This research aims to know and analyze the influence of leverage on dividend policy with firm size and profitability as a mediating variable. This research was conducted on the agriculture sector listed on Indonesia Stock Exchange (IDX) period 2014-2018. The agriculture sector was chosen because his activities on IDX more fluctuate than another sector however, Product Domestic Bruto (PDB) rose consistently during 2014-2017. The type of this research is causal research with a quantitative approach. The population of this research is the agriculture sector listed on IDX period 2014-2018. The population in this research as many as 18 companies. This research sampled using a purposive sampling technique and retrieved nine companies as a sample. Methods of data analysis used in this research using Path Analysis with SmartPLS 3.0 analysis tools. This research found that leverage statistically significant positive to profitability, leverage does not affect the firm size and dividend policy, firm size statistically insignificant to dividend policy, profitability statistically insignificant to dividend policy. Both firm size and profitability can not be mediating variable between leverage and dividend policy. The result of this study hopefully can be used by companies agriculture sector to determine dividend policy. For investors, it is expected that it can be considered before investing.